Cirolanides wassenichae sp. nov., a freshwater, subterranean Cirolanidae (Isopoda, Cymothoida) with additional records of other species from Texas, United States - Schwartz, Benjamin F.; Hutchins, Benjamin T.; Schwartz, Zachary G.; Hess, Alexander J.; Bonett, Ronald M. (Zootaxa, 2019)
Cirolanides wassenichae sp. nov., is described from the phreatic zone of the Edwards Aquifer, Texas, USA where it is sympatric with Cirolanides texensis Benedict, 1896. Its status as a new species is based on both morphological and molecular data. Number of antennula articles (3–5 vs 9–15), size (mean sizes of 9.5 and 8.8 mm vs 11.1 and 10.4 mm for males and females, respectively), morphology of pereopods 1–3 (haptorial to semi-haptorial in 1–3 vs only 1 haptorial), and shape of pleotelson (squared, slightly indented vs rounded) are key morphological characteristics that distinguish C. wassenichae sp. nov. from C. texensis. Phylogenies based on cytochrome oxidase 1 and large ribosomal subunit 28S show that divergent morphologies correspond to reciprocally monophyletic groups for both nuclear and mitochondrial datasets. The genus Cirolanides is in need of revision, as our description of C. wassenichae sp. nov. renders C. texensis paraphyletic.